2009
DOI: 10.1007/s10802-008-9292-y
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Functioning in Boys with Attention-Deficit/Hyperactivity Disorder: Examining Subtypes of ADHD and Associated Comorbid Conditions

Abstract: Disruptions to hypothalamic-pituitary-adrenal (HPA) axis function have been associated with varying forms of psychopathology in children. Studies suggesting children with ADHD have blunted HPA function have been complicated by the prevalence of comorbid diagnoses and heterogeneity of ADHD. The goals of this research were to assess the relations between waking and stress-response salivary cortisol levels and comorbid disruptive behavior (DBD) and anxiety (AnxD) disorders and problems in boys with ADHD, and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 51 publications
4
46
2
Order By: Relevance
“…Some authors confirmed a hypo-arousal pattern in children with ADHD+ODD measuring both awakening (Freitag et al, 2009) and basal values (Kariyawasam et al, 2002) while other authors failed to find any robust association between waking levels and comorbid problems in ADHD (Hastings et al, 2009). In line with these findings, no differences in basal levels between ADHD children with aggression and without aggression have been reported (Schulz et al, 1997), suggesting the possibility that certain characteristics of ADHD, rather than aggression, could be associated with cortisol levels.…”
Section: <Insert Table 3 About Here>mentioning
confidence: 85%
“…Some authors confirmed a hypo-arousal pattern in children with ADHD+ODD measuring both awakening (Freitag et al, 2009) and basal values (Kariyawasam et al, 2002) while other authors failed to find any robust association between waking levels and comorbid problems in ADHD (Hastings et al, 2009). In line with these findings, no differences in basal levels between ADHD children with aggression and without aggression have been reported (Schulz et al, 1997), suggesting the possibility that certain characteristics of ADHD, rather than aggression, could be associated with cortisol levels.…”
Section: <Insert Table 3 About Here>mentioning
confidence: 85%
“…Cortisol then acts on the hypothalamus, pituitary, and hippocampus to inhibit its own production in a negative feedback loop. It has been reported that children with ADHD have a blunted cortisol response to psychosocial stressors, a decreased cortisol awakening response (CAR), or lower plasma daytime cortisol (King et al 1998;Ma et al 2011;Randazzo et al 2008;Scerbo and Kolko 1994;van West et al 2009), though there is considerable inconsistency between studies (Freitag et al 2009;Hastings et al 2009;Snoek et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Diminished wakening cortisol was not observed in children with ADHD only or in children with ADHD plus conduct disorder or anxiety disorder (Freitag et al, 2009). In other studies, in this case 170 elementary school-age ADHD males, no differences in baseline, waking cortisol levels between ADHD subtypes could be demonstrated (Hastings et al, 2009). …”
Section: Dysregulation Of Hypothalamic -Pituitary -Adrenocortical Aximentioning
confidence: 55%
“…increased stressed cortisol levels in response to venipuncture are greater in some ADHD children with coexisting anxiety disorders than in those with comorbid disruptive behavior or oppositional problems (Hastings et al, 2009).…”
Section: Dysregulation Of Hypothalamic -Pituitary -Adrenocortical Aximentioning
confidence: 92%
See 1 more Smart Citation